EFFICIENCY OF HEAT UTILIZATION OF WASTEWATER OF “SHURTAN GASCHEMICAL COMPLEX” ENTERPRISE - Abdurakhmanova, Nasiba; Tashmamatov, Bobir (Innovatsion texnologiyalar, 2024)
In the world, there are strong trends in the use of renewable energy sources (RES) in the creation of energy-efficient systems of management of heat and fuel-energy resources. In this article, by utilizing the heat of secondary energy sources (wastewater) of “Shurtan GasChemical Complex” LLC on the basis of RES and heat pump devices (HPD), the objects of the enterprise “Shurtan GChC” LLC with additional heat energy and purified technical water the possibility of provision was considered. The authors conducted an experimental study of the physico-chemical and technological parameters of waste water in this article. The quantity and heat capacity of waste water, in the calculation of the efficiency of utilization of low-temperature waste water heat in the heat supply systems of the enterprise “Shurtan GChC” LLC, heat-traditional methods such as technical and calculation were used. According to the authors, the enterprise “Shurtan GChC” LLC increased the heat capacity of low-temperature wastewater, purified technical water for technological processes, and provided the heat of the enterprise’s facilities with solar-thermal (steam compressor heat pump (SCHP) heat of low-temperature wastewater Technological schemes of disposal, heat and purified technical water are proposed in the SCHP) method, based on their heat capacity and energy efficiency. Taking into account the parameters of the meteorological climate of Kashkadarya region, as a result of the utilization of the heat of the low-temperature wastewater of the proposed “Shurtan GChC” LLC by the SCHP method, 350⁓400 tons of conventional fuel (coal) will be saved per year.